Methodology for Organising the Process of Collecting Consolidated Evidence for the Ruination Registry Using Aerial Photography, Taking Into Account All Stages and Types of Operations - Horelyk, S.; Nechausov, A.; Levchenko, M. (Land Management, Cadastre and Land Monitoring, 2024)
The armed aggression of the Russian Federation against Ukraine has led to significant destruction of the residential and municipal infrastructure of cities and towns not only in the occupied territories, but also in territories throughout the country due to massive rocket attacks. The problem of damage estimation for people who have lost their homes or have partial damage to their homes has a priority status, as the number of people staying in the streets is constantly growing, and social temporary housing is running out of space, as it is becoming permanent for them. Therefore, any state initiatives to compensate or rebuild people’s housing and restore municipal institutions and facilities that are important for the restoration of normal life in the de-occupied territories and territories of the country that suffer the greatest damage from aggression should find active support, both practical and analytical, among the scientific community and legal entities that are able to implement the state’s initiatives in a short time. Thus, the article proposes a methodological framework for the practical implementation of the state initiative to effectively and substantiated by factual evidence (aerial photographs, orthophotographs, vectorised and decoded typical signs of destruction) allocate funds for the restoration and reconstruction of damaged property to people who have experienced material losses and have no place to live. The purpose of the study is to develop a methodology for collecting and cataloguing consolidated evidence for the register of destruction using aerial photography, taking into account all stages and types of work in the conditions and with regard to the conduct of hostilities. The main objectives of the study are: to analyse existing methods for determining the geometric characteristics of the consequences of military shells hitting buildings; to determine the relationship between the force of the explosion and the geometric characteristics of damage; to develop a methodology for determining the degree of damage to a building and assessing damage; to create and implement technologies for processing and cataloguing typical damage data; to develop forms of reporting documentation based on the data sets obtained, taking into account the further needs of the state; to test the developed methodology in practice. The developed methodology will optimise the process of obtaining and processing the necessary data from the mission planning stage to the damage assessment stage, based on the processed data and technical reports of the analyst team by creating a single and universal methodology that minimises numerous differences in the standardisation of input data, will create a single effective data collection system throughout the country and will accelerate the process of recording and confirming cases requiring state intervention at the state level. The effectiveness and accuracy of the proposed methodology is due to the modern software and analytical products of geoinformation technologies and effective technological means of field work for obtaining remote sensing data. Keywords: damage, aerial photography, unmanned aerial vehicles, remote sensing of the Earth, military aggression by russia.